From fascism to libertarian communism : Georges Valois against the Third Republic - Douglas, Allen, 1949- (Berkeley : University of California Press, 1992)
Georges Valois is the enigma who stands at the center of French fascism. Writer, publisher, economic and political organizer, Valois went from adolescent anarchism to fascism and finally to libertarian socialism. His career has mystified scholars, as it did his contemporaries. From Fascism to Libertarian Communism is the first study of Valois to take his entire life and work as its focus, explaining how certain basic assumptions and patterns of thought took form in strikingly different ideological options. Douglas's work, based on a thorough examination of sources from police archives to personal papers and interviews, provides a convincing explanation of this quixotic figure--a man who founded French fascism only to turn to the radical left and eventually die as a resister in Bergen-Belsen. At a time when radical socialism is in decline and neofascist movements are gaining renewed support--in France and elsewhere--this original interpretation of Georges Valois's life and thought could not be more timely.
Frontmatter -- Contents -- Acknowledgments -- Introduction -- ONE. Childhood and Youth -- TWO. Valois in the Action Française, I -- THREE. Valois in the Action Française, II -- FOUR. The Faisceau, I -- FIVE. The Faisceau, II -- SIX. The Faisceau, III -- SEVEN. The Years of Respectability -- EIGHT. Everything Is Possible -- NINE. War or Revolution -- TEN. Revolution or Defeat -- ELEVEN. Occupation and Resistance -- Conclusion -- Abbreviations -- Notes -- Bibliography of Works Cited -- Index
Includes bibliographical references (pages 309-316) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Valois, Georges, -- 1878-1945.; Valois, Georges, -- 1878-1945; France -- Politics and government -- 20th century; Right and left (Political science); Politicians -- France -- Biography; France -- Politique et gouvernement -- 20e siècle.; Politiciens -- France -- Biographies; HISTORY; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY / Europe / General; Politics and government; Politicians; Right and left (Political science); France; 1900-1999; anarchism; anarchy; autobiography; economic organizer; famous publisher; famous writer; french facism; french republic; french revolution; libertarian socialism; memoir biography; neofascist movement; personal papers; police archives; political organizer; radical political movements; radical socialism; renewed support; socialism and communism; Biographies; Biografieën (vorm); Biographies; Biographies